Inter‐ and intra‐rater reliability of ultrasound tissue characterization (UTC) in patellar tendons. (22nd May 2019) - van Ark, Mathijs; Rabello, Lucas Maciel; Hoevenaars, Dirk; Meijerink, Joost; van Gelderen, Niels; Zwerver, Johannes; van den Akker‐Scheek, Inge
Abstract : Purpose: Ultrasound tissue characterization (UTC) is used in research and clinical practice to quantify tendon structure of the patellar tendon. This is the first study to investigate the inter‐ and intra‐rater reliability for UTC of the patellar tendon on a large scale. Method: Fifty participants (25 patellar tendinopathy, 25 asymptomatic) were recruited. The affected patellar tendons in symptomatic and right tendons in asymptomatic participants were scanned with UTC twice by one researcher and once by another. The same was done for contour marking (needed to analyze a UTC scan) of the tendon. Intraclass correlation coefficient (ICC (2, 1)) for echo‐types I, II, III, IV, aligned fibrillar structure (echo‐types I + II), and disorganized structure (echo‐types III + IV) were calculated. This was done for UTC scans as well as solely marking contours. Results: Inter‐rater reliability showed fair to good ICC values for echo‐types I (0.65) and II (0.46) and excellent ICC values for echo‐type III (0.81), echo‐type IV (0.83), aligned fibrillar structure (0.82), and disorganized structure (0.82). Intra‐rater reliability showed excellent ICC values for echo‐types I (0.76), III (0.88), IV (0.85), aligned fibrillar structure (0.88), and disorganized fibrillar structure (0.88) and a fair to good value for echo‐type II (0.61). Contour marking showed excellent ICC values for all echo‐types. Conclusion: This study showed that UTC scans for patellar tendons have overall good intra‐rater and inter‐rater reliability. To optimize reliability of UTC scans of the patellar tendon, using the same rater and using aligned fibrillar structure (echo‐types I + II combined) and disorganized structure (echo‐types III + IV combined) as outcome measures can be considered.